2009
DOI: 10.1007/s00270-009-9511-0
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Treatment of Central Venous Stenosis in Hemodialysis Patients: Long-Term Outcomes

Abstract: The purpose of this study was to evaluate the long-term outcomes of endovascular treatment of central venous stenosis in patients with arteriovenous fistulas (AVFs) for hemodialysis. Five hundred sixty-three patients with AVFs who were referred for a fistulogram were enrolled in this study. Among them, 44 patients showed stenosis (n = 35) or occlusions (n = 9) in the central vein. For the initial treatment, 26 patients underwent percutaneous transluminal angioplasty (PTA) and 15 patients underwent stent placem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 31 publications
1
55
0
1
Order By: Relevance
“…8,9) On the contrary, other groups reported that the primary patencies between angioplasty and stent were not significantly different. 10,11) Further, Ozyer et al 12) reported that stent placement for central venous stenosis or occlusion led to a significantly lower primary patency rate than PTA but added to the longevity of vein patency in angioplasty-resistant lesions; therefore, stent placement should be considered in such angioplasty-resistant lesions. The most commonly used stents for central venous stenosis or occlusion are self-expandable stents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9) On the contrary, other groups reported that the primary patencies between angioplasty and stent were not significantly different. 10,11) Further, Ozyer et al 12) reported that stent placement for central venous stenosis or occlusion led to a significantly lower primary patency rate than PTA but added to the longevity of vein patency in angioplasty-resistant lesions; therefore, stent placement should be considered in such angioplasty-resistant lesions. The most commonly used stents for central venous stenosis or occlusion are self-expandable stents.…”
Section: Discussionmentioning
confidence: 99%
“…Palmaz stent placement was successfully performed for the stenosis employing the pull-through technique, in which a guidewire was passed from the left internal jugular vein to the access vein. There has been one report of a stent being placed for central venous occlusion or stenosis with the use of the pull-through technique between the femoral vein and access vein 11) . To our knowledge, however, there has been no report of stent placement employing the pull-through technique from the left internal jugular vein to the access vein for subclavian venous stenosis in an HD patient with a PLSVC.…”
Section: Discussionmentioning
confidence: 99%
“…Placement of stents in this position remains controversial. Kim et al 13 have reported that angioplasty restenosis rates are similar with and without stents. Kwok 14 recommends that stents should be reserved for cases of recoil or restenosis within 3 months of angioplasty.…”
Section: Arteriovenous Fistulamentioning
confidence: 94%
“…the entire length of the artery from the origin from the aorta to the arteriovenous anastomosis, the arteriovenous anastomosis (in the case of AVG, the entire graft), and the central vein (draining vein)up to the confluence with the vena cava. 13,18,20,21,30,38,49,78,93 The types of lesions considered to be targets are stenosis, lesions requiring treatment, including both thrombotic and non-thrombotic occlusions. However, in cases involving a central artery or vein, which are likely to require emergency hemostasis if the blood vessel is damaged, each medical facility must determine whether VAIVT is indicated based on the facility s abilities, including whether they have covered stents for hemostasis or surgical backup available.…”
Section: Subjects and Indicationsmentioning
confidence: 99%
“…Although there is some debate over indications, currently indications on which there is a relative amount of consensus are as follow 3,4,12,13,14,15,30,34,64,66,67,83,84 1. Cases of elastic recoil in which at least 30% of the stenosis remains regardless of the fact that full expansion of a balloon of appropriate diameter was possible.…”
Section: Descriptionmentioning
confidence: 99%